1993
DOI: 10.1063/1.354254
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and growth process of thermally induced oxide precipitates in Czochralski silicon

Abstract: The morphology and growth process of oxide precipitates in Czochralski silicon have been studied with prolonged thermal treatments up to 700 h at intermediate temperatures (700–900 °C). It was found with transmission electron microscopy observation that (i) the morphology of precipitates changes from platelet to aggregation of polyhedra at both 800 and 900 °C during isothermal heat treatment, and (ii) the growth of platelet precipitates follows a t1/2 law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 19 publications
5
66
0
6
Order By: Relevance
“…15. It seems that with increasing temperature the thickness of the plate-like precipitates increases until they become octahedral as the ones we observed in the sample with growth anneal for 2 h at 1100…”
Section: Resultssupporting
confidence: 52%
“…15. It seems that with increasing temperature the thickness of the plate-like precipitates increases until they become octahedral as the ones we observed in the sample with growth anneal for 2 h at 1100…”
Section: Resultssupporting
confidence: 52%
“…As can be seen the oxygen precipitates are of platelet morphology, accompanied with stress field rather than secondary induced defects such as punched-out dislocations. It was reported that the platelet oxygen precipitates are generally formed by the moderate length of anneal in the temperature range of 700-1000 1C [18] and the lattice strain around the platelet oxygen precipitates could reach 0.4% [19]. The relationship between the thickness (d) and diagonal length (r) of the platelet oxygen precipitates can be described by the following equation [18]:…”
Section: Characterization Of Oxygen Precipitatesmentioning
confidence: 99%
“…The sizes of oxygen precipitates herein are almost determined by the growth anneal at 1000 1C because the duration of nucleation anneal at 650-800 1C is quite short, which just leads to oxygen precipitate nuclei of small sizes. It has been reported that both thickness and diagonal length of platelet precipitates obey the t 1/2 law (t refers to annealing time), so the aspect ratio (b ¼d/r) depends on the annealing temperature rather than the annealing time [18,20].…”
Section: Characterization Of Oxygen Precipitatesmentioning
confidence: 99%
“…Initially, the precipitates can be assumed to grow as thin plates of constant thickness according to the growth equation given by, where γ is a kinetic coefficient whose value is chosen to be 2 Â 10 À 8 cm which is the same as proposed in [24]. However, Sueoka et al [29] has shown that in very long isothermal annealing treatments at 800 1C, the growth of oxide precipitate plates can be described by the following equations for a thin oblate spheroid,…”
Section: Size Distribution Calculationmentioning
confidence: 98%